1887 N.C. Sess. Laws 885 - (:unkn) unknown (My University, 1885)
Ch. 58, § 22, pt. 50: Imposed a twenty-five dollar property tax on every pistol, Bowie-knife, dirk, sword-cane, or other deadly weapon.
Keywords: TAX - PROPERTY OR SALES